Studies on the shootborer Hypsipyla grandella Zeller. III. The evaluation of some systemic insecticides for the control of larvae in Cedrela odorata L. - Allan, G.G.; Gara, R.I.; Wilkins, R.M. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Continuing the series of studies on Hypsipyla grandella Zelles (Cf. Turrialba 20(1):233-247. 1970), the main pest that hinders the establishment of native Meliaceae in the American Tropics, a study was conducted to evaluate a group of twenty-eight systemic insecticides in the control of H. grandella larvae attacking Cedrela odorata plants. The experiments were carried out in a greenhouse of the Inter-American Institute of Agricultural Sciences, Turrialba, Costa Rica, in two successive stages: first, the characteristic uptake curves of each insecticide in the plant were determined by sampling leaves collected at different times after application of the insecticide to the soil of the plants. The relative toxic levels in the leaves of the plants were then determined by means of standardized bioassay techniques. In the next stage, C. odorata plants treated with equal doses of these systemic agents (75 mg) were exposed to attack by H. grandella larvae (first instar) at the time when toxicant accumulation was at its maximum. The plants were exposed to attack by attaching H. grandella eggs to the leaves as they were about to hatch. The effect of the systemic agents was evaluated 7 days after the eggs attached to the plants, using a "damage factor" based on plant condition and larval mortality Of the 28 systemics tested, five: carbofuran, methomyl, phosphamidon, monocrotophos, and Isolan, gave complete protection. Plants treated with Monitor, nichlorofon, dimethoate, and dicrotophos were damaged, but no larvae survived after 7 days. The other systemics did not give completely satisfactory results. Methomyl and carbofuran were the only systemics that still gave complete protection against attack 23 days after application.